2021
DOI: 10.1371/journal.pone.0245156
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy in Arab states of the Gulf Cooperation Council: A systematic review

Abstract: Background Mental health literacy (MHL) has been relatively neglected, despite the increase of mental health illnesses worldwide, as well as within the Middle East region. A low level of MHL may hinder public acceptance of evidence-based mental health care. Aim This systematic review aims to identify and appraise existing research, focusing on MHL among adults in the Gulf Cooperation Council (GCC) countries. Methods A systematic search of electronic databases (PubMed, PsychInfo, and Medline) was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…In contrast, a systematic review found that factors associated with a lower recognition of mental illness across all demographics included young adults, illiteracy, and females (Elyamani et al, 2021).…”
Section: Ta B L Ementioning
confidence: 89%
“…In contrast, a systematic review found that factors associated with a lower recognition of mental illness across all demographics included young adults, illiteracy, and females (Elyamani et al, 2021).…”
Section: Ta B L Ementioning
confidence: 89%
“…The results showed an overall high level of stigma and negative attitudes towards mental health in the general population. 23 The awareness of the Saudi population has also been assessed regarding bipolar disorder, in a study concluding that 52% had heard of bipolar disorder, 49% did not consider psychiatric medication to be an effective treatment for bipolar disorder, and more than half chose to pray instead of seeking treatment. 24 In 2016, a study concluded that although 87% of people believe that depression is a medical condition requiring treatment, 45.98% believe that antidepressants are addictive.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, it is likely that unpleasant childhood experiences, childhood and adolescent depression and anxiety disorders, societal roles associated with unfavourable experiences, and psychological characteristics linked to susceptibility to life events and coping mechanisms will be implicated. However, it is still difficult to integrate the factors influencing gender differences in mental problems into comprehensive etiological models [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate that the higher the education levels, the better BDI-II and HAM-A scores. In the Middle and Far East, many studies have shown an association between poor education and poor mental health, which is partially mediated by health literacy [ 40 , 51 ]. This could suggest that many recruited participants with clinically significant depressive and anxiety symptoms did not seek medical help as they lack the knowledge about the clinical presentation of mental problems.…”
Section: Discussionmentioning
confidence: 99%